The Influence of Organizational Ideology on Organizational Reputation - Analytical Research in the Ministry of Education - Quinn Dawood Shaheen*, Ahmed; Hassoun Al-Taie , Ali (Journal of Economics and Administrative Sciences, 2024)
The current research aims, through the variables it includes, to test the effectual relationship of organizational ideology on organizational reputation, Provide clarifications about the research variables and identify them more accurately and in detail, within the intellectual, philosophical and applied framework, and build a realistic, simplified and acceptable model, linking the variables and dimensions of the research, consistent with and simulating the reality of the work environment of the researched organization, the research problem represented the challenges that organizations face, These challenges created a problem regarding the ideology of organizations in terms of commitment, organizational loyalty, and conformity of values, This problem was reflected in the level of the organization’s reputation, The researchers took the Ministry of Education as an organization to apply the study to, and the adoption of an intentional sample represented by department managers. Their number reached (112) managers, and the number of valid questionnaires for testing was (109), and the adoption of the questionnaire tool for measurement, and the adopted the statistical methods, which were represented by examining and testing the study measurement tool, descriptive analysis and data iterations, and test the effect between research variables, The most important results have been shown the existence of a positive and direct correlation and influence relationship between the research variables in its study of the reality of the environment of the researched organization, it explains that there is a relationship between organizational ideology in achieving a good organizational reputation for the researched organization.